Development of PR in Kazakhstan and possibilities of periodization (Herald of Journalism, 2016)
The problem of periodization of the Kazakhstan PR, despite of some publications in this area, still remains the most poorly understood and highly controversial area. There are a number of reasons, mainly based on the difficulty of the methodological and technical issues, as well as the fact that domestic public relations passed a way of solving many controversial and problematic tasks. In this article, the authors pay attention to such moments in the development of PR in Kazakhstan, and offer own version of periodization of domestic public relations.